Liver Transplantation for Liver-Originated Malignancy: A Single Center Experience - Ramazan Kozan; M. Hakan Sözen; Aydın Dalgıç (Gazi Medical Journal)
Objective: We aimed to evaluate liver transplantation (LT) effectiveness for liver-originated malignancies, focusing on hepatocellular carcinoma (HCC), at a single center. Methods: Retrospective data review of LT cases between 2006 and 2023. Inclusion criteria: no extrahepatic involvement and liver-originated malignancy. Demographic characteristics, etiology, alpha-fetoprotein (AFP) levels, Milan Criteria compliance, pre-transplant treatments, complications, recurrence, and mortality were analyzed. Results: Fourteen liver-originated tumors underwent LT, half of which were from deceased donors. Hepatitis B virus was the common etiology (71%). The median AFP level was 4 ng/mL. Fifty percent received pre-transplant therapy. Patient survival rates at 1, 3, and 5 years: 72%, 72%, 68% respectively. The recurrence-free survival rates for the same years were 93%. Conclusion: LT, including living donor LT, is effective for liver-originated tumors, especially HCC. Encouraging survival rates align with the Milan and University of California, San Francisco Criteria. Despite limitations, ongoing research is vital for LT’s role in liver cancer management, considering tumor size, positron emission tomography/computed tomography, grade, and AFP levels for candidate selection beyond the current criteria.